Enhancing patient comfort in varicose vein treatment through combined lidocaine and ropivacaine tumescent anesthesia - Li, Yubo; Li, Tan (Frontiers in Surgery, 2024)
Objective: To compare the analgesic effects of specific tumescent anesthetic solutions composed of lidocaine, ropivacaine, or a combination of lidocaine and ropivacaine during endovenous radiofrequency ablation for the treatment of great saphenous vein varicosities. Method: This study included 149 patients with lower limb varicose veins who were admitted to our department between 2019 and 2023. The patients were randomly assigned to three groups: the lidocaine group (Group I), the ropivacaine group (Group II), and the lidocaine + ropivacaine group (Group III). Intraoperative vital signs, intraoperative and postoperative visual analog scale (VAS) pain scores, and long-term treatment outcomes were assessed using the venous clinical severity score (VCSS) based on clinical performance. Results: There were no significant differences in age, body mass index, operative time, or blood loss among the three groups (P ≥ 0.05). The differences in the mean arterial pressure and heart rate during surgery in Group II were significantly greater than those in Groups I and III (P < 0.05). The intraoperative VAS scores in Group II were higher than those in Groups I and III (P < 0.05) and at 8 and 12 h postoperatively. There were no significant differences in VCSS among the groups (P ≥ 0.05).The use of a tumescent anesthetic solution composed of lidocaine and ropivacaine significantly improved patient comfort during the perioperative period without affecting surgical outcomes. This formulation can be considered safe and reliable for preparing tumescent anesthesia solutions.